A review of the tertiary and quaternary changes of sea-level in South Africa with special stress on the evidence in favour of a recent world-wide sinking of ocean-level - Krige, A. V.(Albert Victor),1895-1974 (Stellenbosch : Stellenbosch University, 2012)
Thesis (D.Sc.) -- University of Stellenbosch, 1926.